Latent environmetal damage: lagoon of Huacachina, Ica (Peru) - argota pérez, george (2021)
Heritage areas with tourist attractions that offer ecosystem services must be systematically evaluated for their preservation. The objective of the manuscript addressed to the Editor describes the latent environmental damage in the Huacachina lagoon, Ica-Peru. The contact and physical pressure of the dune on the containment barriers was observed, which could prevent the recreation of passers-by in the future. Likewise, an excessive density of the Scirpus californicus species, which is an indicator of the poor quality of the water and which is corroborated by the high turbidity.